UPAYA PENCEGAHAN PENYEBARAN AFRICAN SWINE FEVER DI NUSA TENGGARA TIMUR - Jeanet Frederika Tamar Lali Pora; Sharoniva J. Koanak; Yusinta V. Nawa; Lucia D. Amleni; Angela N. Daki; Yohanes R. Nadja; Dalmasia T. Dhiu; Maria G. M. Jo; Mario H. Cantona; Diana Agustiani Wuri; Annytha I. R. Detha; Larry R. W. Toha; Novalino H. G. Kallau (Universitas Nusa Cendana, 2021)
The outbreak of African Swine Fever (ASF) disease as a disease that can affect the swine has distributed in many countries including Indonesia. The Province of Nusa Tenggara Timur (NTT) is the biggest swine population in Indonesia being risk because Timor Island directly bordered Timor Leste, which an area that affected ASF. The outbreak of ASF caused a big loss to the economy and the public's fear of consumption of pork and other swine products. The purpose of this activity is to given information about characteristics of good pork quality and appeal public to control and prevent dissemination of ASF. According to this activity, the public knowing ASF as a danger and zoonotic disease, which caused public anxiety to consumption pork and other swine products. Although the public knowing about the danger of ASF, there is no preventive action they know. This activity is a tool for breeders to prevent ASF in their animal husbandry and for the public to know that ASF, not a zoonotic disease. However, consumption of pork and other swine products infected with ASF can spread ASF continuously.